Impact of Introducing a PACU24 Concept on the Perioperative Outcome of Patients with Advanced Ovarian Cancer Treated with Cytoreductive Surgery - Reuter, Susanne; Schmalfeldt, Barbara; Haas, Sebastian A.; Zapf, Antonia; Cevirme, Sinan; Prieske, Katharina; Wölber, Linn; Müller, Volkmar; Zöllner, Christian; Jaeger, Anna (Geburtshilfe und Frauenheilkunde, 2023)
Patients with ovarian cancer who undergo multivisceral surgery usually require intensive care monitoring postoperatively. In view of the ever-fewer numbers of high-care/intensive care beds and the introduction of fast-track treatment concepts, it is increasingly being suggested that these patients should be cared for postoperatively in 24-h Post Anesthesia Care Units (PACU24). No analyses have been carried out to date to investigate whether such a postoperative care concept might be associated with a potential increase in postoperative complications in this patient cohort.A PACU24 unit was set up in our institution in 2015 and it has become the primary postoperative care pathway for patients with ovarian cancer who have undergone cytoreductive (debulking) surgery. A structured, retrospective analysis of data from patients treated before (control group) and after (PACU group) the introduction of this care concept was carried out, with a particular focus on postoperative complications and secondary admission to an intensive care unit where necessary.The data of 42 patients were analyzed for the PACU group and 45 patients for the control group. According to the analysis, the preoperative and surgical data of both groups were comparable (age, ASA, BMI, FIGO stage, duration of surgery, blood loss). The Physiological and Operative Severity Score for the enUmeration of Mortality and morbidity (POSSUM score) as a measure for the risk of postoperative complications was higher in the PACU group (11.1% vs. 9.7%, p = 0.001). Patients in the PACU group underwent bowel resection with anastomosis significantly more often (76.3% vs. 33.3%, p < 0.001), although the extent of surgery was otherwise comparable. The total number, type and severity of postoperative complications and the duration of the overall stay in hospital did not differ between the two groups. None of the patients required secondary transfer from the PACU or normal ward to an intensive care unit (ICU).Our data support the assumption that the care concept of transferring patients to a PACU24 represents a safe and cost-saving care pathway for the postoperative care of patients even after complex gynecological-oncological procedures.Patientinnen mit Ovarialkarzinom und multiviszeralen Eingriffen bedürfen in der Regel einer postoperativen intensivmedizinischen Überwachung. Bei zunehmend angespannten Ressourcen bezüglich High-Care-Intensivbetten und gleichzeitiger Einführung von Fast-Track-Behandlungskonzepten wird eine postoperative Betreuung auch dieser Patientengruppe in 24-h Post Anesthesia Care Units (PACU24) propagiert. Analysen, ob ein solches postoperatives Versorgungskonzept mit einer eventuellen Zunahme von postoperativen Komplikationen in diesem Patientenkollektiv vergesellschaftet ist, liegen bisher nicht vor.In unserer Institution wurde 2015 eine PACU24-Einheit eingeführt und für Patientinnen mit Ovarialkarzinom und einer zytoreduktiven (Debulking-)Operation als primärer postoperativer Behandlungspfad implementiert. Es erfolgte eine strukturierte, retrospektive Analyse der Patientendaten vor (Kontrollgruppe) und nach (PACU-Gruppe) Einführung dieses Behandlungskonzepts insbesondere in Bezug auf postoperative Komplikationen und gegebenenfalls notwendige, sekundäre Aufnahme auf eine Intensivstation.In der PACU-Gruppe wurden 42 Patientinnen analysiert und in der Kontrollgruppe 45 Patientinnen. Beide Gruppen zeigten in der Analyse vergleichbare präoperative und chirurgische Daten (Alter, ASA, BMI, FIGO-Stadium, Dauer der Operation, Blutverlust). Der „Physiological and Operative Severity Score for the enUmeration of Mortality and morbidity“ (POSSUM-Score) als Maß für das Risiko bezüglich postoperativer Komplikationen war in der PACU-Gruppe höher (11,1% vs. 9,7%, p = 0,001). Patientinnen aus der PACU-Gruppe erhielten relevant häufiger Darmresektionen mit Anastomosen (76,3% vs. 33,3%, p < 0,001) bei sonst vergleichbarem Operationsumfang. Die Gesamtzahl, Art und Schweregrad der postoperativen Komplikationen und die Dauer des Gesamtkrankenhausaufenthalts unterschied sich in beiden Gruppen nicht. Keine Patientin musste sekundär von PACU oder Normalstation auf Intensive Care Unit (ICU) verlegt werden.Unsere Daten unterstützen die Annahme, dass das Behandlungskonzept einer PACU24 einen sicheren und ressourcensparenden Behandlungspfad für die postoperative Versorgung von Patientinnen auch nach komplexen gynäkoonkologischen Eingriffen darstellt.
Keywords: PACU24; Fast Track (multimodale perioperative Patientenversorgung); Länge des Krankenhausaufenthaltes (Hospitalisationslänge); zytoreduktive Chirurgie; Ovarialkarzinom